Clinical neurological findings among car painters exposed to a mixture of organic solvents. - Husman, Kaj; Karli, Pauli (Scandinavian Journal of Work, Environment & Health, 1980)
A full clinical neurological examination was used to study the possible effects of long-term exposure to low concentrations of mixtures of organic solvents on the nervous system. The exposed group consisted of 102 male car painters and the referents of 102 age- and sex-matched locomotive engineers and assistants. The psychoorganic syndrome, a decrease in the sense of light touch and pain, and an increase in the vibration threshold were more frequent among the car painters than among the referents, and the observed differences of these frequencies were statistically significant. The sense of vibration had been affected in the lower extremities of 65 of the 102 car painters and in 25 of the referents. Sensory functions seem to be the most vulnerable part of the nervous system of workers chronically exposed to different organic solvents.
Keywords: affection; car painter; central nervous system; clinical neurological finding; exposure; impairment; neurological finding; neurotoxicity; organic solvent; peripheral nervous system; sense of vibration; vibration